2005
DOI: 10.1002/ajmg.a.30600
|View full text |Cite
|
Sign up to set email alerts
|

XK‐aprosencephaly and related entities

Abstract: We offer further biological characterization of the XK atelen/aprosencephaly syndrome in two infants, one with prolonged survival, the other presenting prenatally with apparent hydranencephaly and an orbital tumor (OS). Familial occurrence in the former born to presumably nonconsanguineous Lybian parents may represent parental germinal mosaicism or autosomal recessive inheritance. Both had apparently normal chromosomes; however, the Lybian infant had slightly increased induced chromosome breakage suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Cyclopia, (Lurie et al,1979), cebocephaly (Young et al,1986), and median cleft lip (Adkins and Kaveggia,1979) have been observed. Extensive reviews with references are those of Cohen (1989b) and Renzetti et al (2005). The best anatomic studies are those of Siebert et al (1986,1987).…”
Section: Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopia, (Lurie et al,1979), cebocephaly (Young et al,1986), and median cleft lip (Adkins and Kaveggia,1979) have been observed. Extensive reviews with references are those of Cohen (1989b) and Renzetti et al (2005). The best anatomic studies are those of Siebert et al (1986,1987).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Holoprosencephaly has been reviewed extensively elsewhere (DeMyer et al,1963,1964; DeMyer,1977; Matsunaga and Shiota,1977; Barr et al,1983; Siebert et al,1986,1987; Cohen,1989a,1989b; Siebert et al,1990; Cohen and Sulik,1992; Martínez‐Frías et al,1994; Croen et al,1996; Rasmussen et al,1996; Ming and Muenke,1998; Roessler and Muenke,1998; Barr and Cohen,1999; Wallis and Muenke,1999; Muenke and Cohen,2000; Cohen,2001a; Muenke and Beachy,2001; Barr and Cohen,2002; Cohen,2002; Cohen and Shiota,2002; Cohen,2003,2004,2005; Stashinko et al,2004; Renzetti et al,2005).…”
Section: Introductionmentioning
confidence: 99%
“…There have been no previous reports of fetal MRI findings of atelencephaly; however, there has been one case of fetal MRI findings very briefly described in XK-aprosencephaly, which described the appearance of an "empty head" with a normal cerebellum. In this particular case, pathology confirmed the presence of a small remnant of neural tissue extending rostrally from an essentially normal cerebellum to the eyes [7]. It is possible that this remnant of neural tissue was too small to be visualized on fetal MRI.…”
Section: Discussionmentioning
confidence: 63%
“…For this reason, aprosencephaly/ atelencephaly has been described as a continuum between anencephaly and holoprosencephaly, characterized by early failure of the neural tube to form a normal prosencephalon [6]. This condition is rare, with an estimated 10 previously reported cases of atelencephaly by Harris et al [2] in 1994 and 20 cases of XKaprosencephaly syndrome by Renzetti et al [7] in 2005, though it is likely that the incidence is much greater as this condition is frequently mislabeled given its rarity. The XK-aprosencephaly syndrome was first described in 1979 by Lurie et al [4] as a combination of three anomalies: 1) aprosencephaly, 2) limb anomalies and 3) genital abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation